Borrowing and Spending in the Money: Debt Substitution and the Cash-Out Refinance Channel of Monetary Policy - Anenberg, Elliot; Scharlemann, Tess; van Straelen, Eileen (American Economic Review, 2025)
We show that the strong negative effect of higher mortgage rates on cash-out refinancing reflects substitution into other borrowing products, not large changes in total new household borrowing. We exploit plausibly exogenous changes in interest rates due to unconventional monetary policy surprises to show that changes in cash-out and other borrowing are roughly offsetting. The elasticity of new household borrowing with respect to mortgage rates is low and varies little with the borrower’s outstanding mortgage rate. Our results suggest that the cash-out refinance channel of unconventional monetary policy is weak and not path dependent. (JEL E43, E52, G21, G51)